PENGARUH PARITAS DAN MEDIA KONSELING MASA NIFAS TERHADAP KEMAMPUAN PERAWATAN MANDIRI IBU POST PARTUM DI BPM VIVI SURABAYA - Yunik Windarti; Uke Maharani Dewi (Universitas Nahdlatul Ulama Surabaya, 2018)
In Indonesia Maternal Mortality Rate (MMR) is still high. Various attempts were made by the government to reduce AKI one of them with the implementation of adequate postnatal care. The success of postnatal care is determined by the mother's ability to care for him, especially since birth experience (parity) and the delivery of health information (media counseling) is good. The aim of research to determine the effect of parity and media postnatal counseling on self-care ability of others. postpartum Analytical research design. The population postpartum mothers day 1-10 for 30 people in BPM Vivi in April-June 2017, the sample size of 30 people were taken to the technique of